A License to Issue (Anywhere) : Patterns and Drivers of Corporate Bonds in Latin America - Vtyurina, Svetlana (IMF Working Papers; Working Paper ;, 2017)
This paper overviews patterns in bond issuance in local and external markets by firms in six large Latin American countries. Data suggest that despite rising issuance, local markets remain small and shallow in several countries. Nevertheless, since greater funding is available to many firms in both markets, we investigate the factors that may explain the firm's choice on where to issue a bond. Using an unbalanced panel of firm and market-level indicators for years 1995-2015, we control for variables representing several theories of capital structure, and the results show that firm characteristics such as size and liquidity increase the likelihood of firms to issue externally. With respect to market characteristics, the market completeness hypothesis generates the most support, where market scale and depth are most important for the issuer's choice of the market, suggesting that local markets will have to become deeper to draw more firms and investment.